Modeling economic growth in contemporary Slovakia - Augustín, Michael,; Jančovič, Peter,; Sergi, Bruno S., (Entrepreneurship and global economic growth., 2024)
Following the peaceful dissolution of Czechoslovakia, the Slovak Republic emerged as an independent nation and embarked on a journey of economic transition and reform. During the thirty early years of independence, Slovakia faced many challenges, including establishing new economic policies, institutions, and legal frameworks. Modeling Economic Growth in Contemporary Slovakia analyses various aspects of Slovakia's economy, including recent developments and events such as the COVID-19 pandemic and war in Ukraine. The chapters also highlight issues that arise from the current economic model, making it difficult for Slovakia to revitalize and adapt the economy to new circumstances. This volume is a must-read for professionals and academics who wish to comprehend the basis of Slovakia's growth and forecast its viability in the coming years. Entrepreneurship and Global Economic Growth presents modern examinations of economic growth at national, regional, and global levels. Each book in this series discusses different dimensions of the changing economic and industrial contexts and examines in detail their impact on the nature of growth and development.